Overview of Ischemic Stroke Risk Factors in the Neurology Ward Patient of Arifin Achmad Hospital, Riau Province - Yossi Maryanti; Enny Lestari; Riki Sukiandra; Nadia Salvira; Rahma Dani; Ahza Chairum Mulia (Nusantara Science and Technology Proceedings, 2022)
Stroke is a disease that continues to be one of the leading health problems in Indonesia and throughout the world. Stroke is the second leading cause of death and the leading preventable cause of disability after heart disease. Risk factors have an essential role in the occurrence of stroke. Control of risk factors is an important factor in the treatment of stroke. This study aims to describe the risk factors of ischemic stroke patients treated in the neurology ward of Arifin Achmad Hospital, Riau Province. This research is descriptive by looking at data from medical records from July 2022 until October 2022. The inclusion criteria were all stroke patients who were treated at the Arifin Achmad Regional Hospital, Riau Province, the exclusion criteria were patients with incomplete data. The data were processed and then analyzed. This study obtained a sample of 60 people. In this study, the number of male samples was 34, and the female sample was 26. Based on the risk factors, 22 patients (36.7%) had a history of hypertension, one patient (1.7%) had a history of diabetes mellitus (1.7%), two patients (3.3%) had a history of heart disease, four patients (6.7) had a history of smoking, and 31 patients (51,7%) patients had a history of mixed risk factors (having more than one risk factor). From this study, it can be concluded that ischemic stroke patients treated in the neurological ward of Arifin Achmad Hospital, Riau Province, mostly have more than one risk factor for stroke occurrence.